in vitro Evaluation of Antioxidant Activity of Phytochemical Extracts from Different Varieties of Various Plants - Parveen*, Rashida; Akhtar, Naveed (Asian Journal of Chemistry, 2013)
In the present study, we examined the comparison of antioxidant activity of six different varieties of three different plants, which were Punica granatum (red and white), Carica papaya (red and yellow) and Lycopersicon esculentum (greenish and red), extracts in different solvents as well as different techniques used for the preparation of plants extracts. We also investigated the secondary metabolites present in different varieties of Punica granatum (red and white), Carica papaya (red and yellow) and Lycopersicon esculentum (greenish and red). The extraction of peel of Punica granatum (red and white) by using 50 % aqueous ethyl alcohol in 1:1 solvent ratio, pulp of Carica papaya (red and yellow) with hexane:ethanol:methanol in 1:1:1 solvent mixture and Lycopersicon esculentum (greenish and red) with hexane:ethanol:acetone in 2:1:1 ratio of solvents. The free radical scavenging activity is determined by using DPPH method and different phytochemical tests were performed to investigate the secondary metabolites. It was resulted that 50 % ethyl alcohol w/v peel extract of Punica granatum extract showed 84 % free radical scavenging activity and the percentage of antioxidant activity Lycopersicon esculentum and Carica papaya extracts were 79 and 73 %, respectively. The different phytochemical tests showed that different active secondary metabolites are present in Punica granatum (red and white), Carica papaya (red and yellow) and Lycopersicon esculentum (greenish and red) plant extracts which are necessary for biological process of life.